2013
DOI: 10.4038/sljch.v42i4.6262
|View full text |Cite
|
Sign up to set email alerts
|

Trauma symptoms in children after the tsunami

Abstract: Limited research has examined factors associated with psychological distress following natural disasters among non-Western child populations. Conditions associated with trauma-related symptoms following the 2004 tsunami in a sample of 265 Sri Lankan child survivors (53.6% female, aged 3 to 17) were examined retrospectively. Multivariate regression analyses identified pre-traumatic conditions (female gender, prior health) and peritraumatic conditions (loss of family, complete property loss) as being associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Most of those are acute and self-limiting, but a certain proportion of disaster victims will go on to develop more severe and enduring conditions such as posttraumatic stress disorder (PTSD), depression and substance misuse (5). Prevalence rates of PTSD, depression, anxiety were 21%, 16% and 30% respectively among Sri Lankan adults and prevalence of PTSD among children was 19% -53.6% following the tsunami in 2004 (6)(7). A recent study done among survivors of the Aranayaka landslide in 2016 reported a 21% prevalence rate of depression (8).…”
mentioning
confidence: 99%
“…Most of those are acute and self-limiting, but a certain proportion of disaster victims will go on to develop more severe and enduring conditions such as posttraumatic stress disorder (PTSD), depression and substance misuse (5). Prevalence rates of PTSD, depression, anxiety were 21%, 16% and 30% respectively among Sri Lankan adults and prevalence of PTSD among children was 19% -53.6% following the tsunami in 2004 (6)(7). A recent study done among survivors of the Aranayaka landslide in 2016 reported a 21% prevalence rate of depression (8).…”
mentioning
confidence: 99%